P-93 Specialist palliative care input in patients with parkinson's disease. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Owen, Rebecca; Ward, Jason
Abstract : Background: Parkinson's disease (PD) is a common, chronic, progressive neurological condition (NICE, 2006). Its prevalence rate in 2009 was calculated as 27.4/10, 000 and is predicted to increase by 28% by 2020 (Parkinson's UK). NICE guidance for PD recommend that palliative care should be considered throughout all phases of the illness (NICE, 2006). Methodology: The audit reviewed all patients over a three-year period who were referred to St Gemma's Palliative Care Services between October 2013 and October 2016. The computer database SystmOne was used to capture patients who had a coded diagnosis of PD. Results: A total of 38 patients were referred to Palliative Care Services, of whom 20 were still alive at point of collection. There were equal numbers of male and female patients referred and the mean age at referral was 78 years. The mean average documented time from diagnosis to death was 8 years. The average time from referral to death was 6.419 months. However, to specifically focus on the 18 patients who died, eight were referred to palliative care services within the last one month of life and four were referred within the last week. The most common referral reasons to palliative care services were request for help with advance care planning (ACP), marked decline in physical function and dysphagia. Of the patients that were referred, 76% (29/38) had documentation of ACP and 63% (24/38) had documentation of DNACPR decision and Gold Standard Framework recommendations. 15/18 patients of those who died had documentation of ACP. Discussion: Patients with PD are much more likely to be referred to specialist palliative care services in the last phases of their illnesses despite NICE guidance. Despite good working relationships with the PD Nurse Specialists, the subgroup of patients referred is a much smaller cohort in comparison to the incidence of PD throughout Leeds.